The richer, the poorer : how Britain enriched the few and failed the poor : a 200-year history - Lansley, Stewart (Policy Press, 2022)
This landmark book charts the rollercoaster history of both rich and poor, and the mechanisms that link them. Stewart Lansley examines the ideological rifts that have driven society back to the divisions of the past and asks why rich and poor citizens are still judged by very different standards.